2008
DOI: 10.5005/jp-journals-10005-1002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malocclusion Among School Children in Bangalore, India

Abstract: The objective of this study was to determine the prevalence of malocclusion among school children of Bangalore city, India during their mixed dentition period. The sample consisted of 745 children (388 males and 357 females) in the age group of 8-12 years randomly selected from twelve different schools in Bangalore city. The subjects were randomly selected, and none had received previous orthodontic treatment. Occlusal anteroposterior relationships were assessed based on the Angle classification. Also various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 4 publications
7
13
0
Order By: Relevance
“…This is similar to the findings of Das et al2 who reported 62% class I malocclusion and 7% class II Div 1 malocclusion. The prevalence of class II Div 2 and Class III malocclusion were low, i.e.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is similar to the findings of Das et al2 who reported 62% class I malocclusion and 7% class II Div 1 malocclusion. The prevalence of class II Div 2 and Class III malocclusion were low, i.e.…”
Section: Discussionsupporting
confidence: 92%
“…This is somewhat similar to the findings of Das et al,2 who conducted an epidemiological study of malocclusion in the age group of 8-12 years in Bangalore city in 2008, and reported a high incidence of malocclusion of 71%. The findings of the present study are in disagreement with those of Kharbanda et al3 who have found 36.6% prevalence of malocclusion in Delhi, while Sidhu4 in his study found higher prevalence rate of Angle’s malocclusion of 90% in the age group of 6-30 years.…”
Section: Discussionsupporting
confidence: 91%
“…Many studies have been done since then worldwide by Chiavaro A [12], Korkhaus G [30], Altemus LA [31], Horowitz et al [32] and many others. These studies showed a higher prevalence of malocclusion than in Indian population when compared with studies done during the same period in India by Shourie KL, Miglani, Tiwari A and others who observed 19.6-37.52% as the prevalence in Punjabi subjects [33].…”
Section: Discussionmentioning
confidence: 57%
“…The prevalence of Class II malocclusion in India varies from 1.9% in Rajasthan 6 to 4.6% in Bangalore34 to 6% in 5-9 year age group and 14.6% in 10-13 years age group in New Delhi [33]. These results were significantly different from those by Emmanuel OA [36], who observed 1.1% as the prevalence of Class II in Benin city, Nigeria and Silva RG et al [35], who observed 21.5% as the prevalence of class II malocclusion in Latino Adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Malocclusion may be defined as a significant deviation from what is defined as a normal or ideal occlusion. Normal occlusion is representative of around 30% to 40% of the population [4,5]. Slight generalized spacing is considered to be normal in primary dentition ( Figure 1).…”
Section: What Is Malocclusion?mentioning
confidence: 99%